Comparative Analysis of Groundwater Quality Across Diverse Sampling Sites in Alwar: Assessing Environmental and Health Implications - Dr.Kamlesh Kumar Dabaria*1, Dr.Meenu Mangal2, Dr. Surendra Kumar Sharma3, Satish Kumar Saini4,Dr. GirjaShanker Tailor5 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Groundwater plays an important role in industrial and agricultural production and social development. In The Present Study, fourteen groundwater samples were collected from different sampling sites (S1, S2, S3, S4, S5, S6, S7, S8, S9, S10, S11, S12, S13&S4) of Alwar (Rajasthan -India). The objective of the study was to determine the groundwater chemistry and analysed for various ground water quality parameters such as pH, EC, TDS, Ca2+, Mg2+, K+Cl-, SO42-, NO3-, F-, BOD, COD, TH, %Na and heavy metals (As, Zn, Fe). The order of abundance of average anions Cl- (233.17mg/l) > SO42- (56.04mg/l) > NO3- (16.1mg/l) >F-(0.70mg/l) and cations in groundwater was found as Mg2+(127.53mg/l)> Ca2+ (101.83mg/l) > K+(9.71mg/l). The study revealed that 64% ground water samples fall into the “hard” category on the basis of total hardness parameters.